2017
DOI: 10.1155/2017/3043061
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Herbal Medicines Used for the Treatment and Management of Human Diseases by Some Communities in Southern Ghana

Abstract: Traditional medicine is an important component of the health care system of most developing countries. However, indigenous knowledge about herbal medicines of many Ghanaian cultures has not yet been investigated. The aim of the present study was to document herbal medicines used by traditional healers to treat and manage human diseases and ailments by some communities living in Ghana. The study was conducted in eight communities in southern Ghana. Data were collected from 45 healers using ethnobotanical questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 30 publications
12
96
1
1
Order By: Relevance
“…In relation to this Boadu A. and Asose A. [18] . affirmed that communities in southern Ghana prepared harvested herbal materials in the form of decoctions and infusions.…”
Section: Medicinal Plants: Preparations and Preservationmentioning
confidence: 65%
See 1 more Smart Citation
“…In relation to this Boadu A. and Asose A. [18] . affirmed that communities in southern Ghana prepared harvested herbal materials in the form of decoctions and infusions.…”
Section: Medicinal Plants: Preparations and Preservationmentioning
confidence: 65%
“…Almost all of the herbalists unanimously agreed that plants are collected at dawn or in the early morning without taking a meal and passing urine. Contrary to this Boadu A. and Asase A [18] indicated that herbalists in southern Ghana are flexible and collect medicinal plants when they are needed, especially in the case of emergency. Besides, herbalists are engaged in harvesting medicinal plants in both dry and wet seasons of the year.…”
Section: Medicinal Plants: Collectionsmentioning
confidence: 92%
“…The route of administration of herbal medicines could be related to bioactive agents in the extracts of the plants (Gurib, 2006). For example, herbal medicines whose bioactive agents are alkaloids are easily assimilated when administered orally while terpenoids especially essential oils are best administered through dermal and/nasal routes (Boadu and Asase , 2017).…”
Section: Administration Methodsmentioning
confidence: 99%
“…Daun selain sebagai tempat berlangsungnya fotosintesis, juga mengandung konsentrasi metabolit sekunder yang sangat tinggi. 21 Kecuali keuntungan farmakologis tersebut, secara teknis daun lebih mudah didapat dan tersedia hampir di setiap waktu, serta memberikan keunggulan komparatif dari segi pelestarian karena bersifat kurang merusak tumbuhan dibanding penggunaan bagian kulit batang, batang atau akar. Bunga, yaitu bunga Cassia alata hanya digunakan oleh satu battra dari etnis Kutai (Kalimantan Timur).…”
Section: Hasilunclassified